The Effectiveness of e-Quran in Improving Tajweed Learning Among Standard Three Pupils in Primary School (Sains Humanika, 2017)
The aim of this study is to identify the effects of e-Quran, as compared to printed Quran, towards the learning of tajweed among pupils in a primary school. A total of 60 samples were selected based on their performance in tests of recitation and memorizing the Quran (the medium and high). The samples were then divided randomly into two groups, i.e. the control group and the experimental group. Independent sample t test were used and the results showed no significant difference between the control group and the experimental group in terms of recitation marks in the Diagnostic (pre-test) and Topical Test (post-test). The survey also found that 48% of respondents who used e-Quran recitation technique increased their performance in learning of tajweed. Those respondents also claimed that they had more fun using the e-Quran materials, as compared to the experimental group who used printed Quran.
Keywords: e-Quran; e-learning; islamic education curriculum; the Koran; Quran recitation; tajweed